Association of polymorphic variants of PTPN22, TNF and VDR systems in children with lupus nephritis: A study in trios of Colombian families (2017)
Introduction: Systemic lupus erythematosus is an autoimmune disease with severity that varies according to race, gender and age of onset. This variation is also observed in genetic markers associated with the disease, present in the PTPN22, VDR, and TNF genes. It is possible that the genetic stratification observed in different populations in the world can be influencing this variability. Objective: To analyze the association and heritability of PTPN22, VDR and TNF gene variants with pediatric lupus nephritis (PLN) in Colombian families. Materials and methods: a study based on 46 trios (Case / parents) was performed. Genotyping by qPCR of variants of rs2476601 in PTPN22; rs361525 and rs1800629 in TNF; TaqI [rs731236], ApaI [rs7975232] BsmI [rs1544410] and FokI [rs2228570] in VDR was performed. The effect of the risk of allele over-transmission through families and linkage disequilibrium of VDR and TNF loci was estimated. Results: We observed that the A allele of rs2476601 in PTPN22 was distributed in 8.69% [n = 16] parents, and increased to 19.5% [n = 18] in cases. Over-transmission of this allele was also observed from parents to offspring 17 times relative to the G allele (p = 0.028). TNF and VDR polymorphisms were not overtransmitted. SNPs TaqI, ApaI y BsmI in VDR showed linkage disequilibrium. Conclusion: These findings seem to demonstrate an association of rs2476601 in PTPN22 with PLN due to its overtransmission in the group of families studied.